Skema Pelepasan Beban Menggunakan Relai Rate of Change of Frequency dengan Supervisi Under Frequency Relay - Adrianti, Adrianti; Nasir, Muhammad; Salvayer, Adiv Rama (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2020)
A Rate of Change of Frequency (ROCOF) relay works based on rate of frequency changes (df/dt) that is a direct indicator of power unbalance between generation and demand. The df/dt indicator make ROCOF relays have a promising opportunity for under frequency load shedding.  Examining the performance of the proposed ROCOF relay scheme for under frequency load shedding become the research objective. The proposed scheme consists of five load shedding steps and they were supervised by Under Frequency Relay (UFR) to avoid mal-operation due to short circuits.  The scheme was assessed using generation loss simulation with contingency of N-1, N-2 and N-2-1 with Digsilent Powerfactory. It is found, for N-1 and N-2 contingencies, the proposed scheme provide better frequency results and faster than UFR scheme. However, there is a problem with the sensitivity of the scheme that is adjusted by delay setting. For light to medium power of generation loss, the required delay is relatively large to obtain the true df/dt value from the measured df/dt that tends to oscillate. However, for severe generation loss, the large delay setting causes the relay to be less sensitive hence a small proportion of the relays do not work at all expected steps.